Enhancement of photocatalytic activity and regeneration of Fe-doped TiO 2 (Ti 1−x Fe x O 2 ) nanocrystalline particles synthesized using inexpensive TiO 2 precursor - Saroj S.; Singh L.; Ranjan R.; Singh S.V. (My University, 2025)
Abstract: Fe-doped TiO 2 , Ti 1−x Fe x O 2 (x = 0.00, 0.01, 0.03, 0.05, 0.07, and 0.09) photocatalysts with enhanced activity were synthesized via a citric-acid-assisted autocombustion method and characterized by X-ray diffraction (XRD) analysis, diffuse reflectance spectroscopy (DRS), Fourier-transform infrared (FTIR) spectroscopy, transmission electron microscopy (TEM), energy-dispersive X-ray spectroscopy (EDS), and X-ray photoelectron spectroscopy (XPS). The photocatalytic activity of the synthesized Fe-doped TiO 2 materials was evaluated using photodegradation of synthetic dye solution (Direct Blue 199) in photochemical and open pan reactors. Among the synthesized Fe-doped photocatalysts, Ti 0.95 Fe 0.05 O 2 showed the highest photodegradation activity. This Fe-doped TiO 2 photocatalyst was regenerated five times and its photocatalytic activity investigated. Graphical abstract: [Figure not available: see fulltext.]. © 2019, Springer Nature B.V.